Revision of the genus Culoptila (Trichoptera: Glossosomatidae) - Blahnik, Roger J.; Holzenthal, R. W. (Zootaxa, 2006)
The caddisfly genus Culoptila is revised to include 17 previously described species and 9 new species. Illustrations of the male genitalia and a key are provided for all species. In addition, illustrations of male head and thoracic features, larval characters and cases, and female genitalia are included. New species described here include: Culoptila bidentata (Costa Rica), C. buenoi (Mexico), C. cascada (Costa Rica), C. hamata (Costa Rica), C. pararusia (Mexico), C. plummerensis (eastern United States), C. tapanti (Costa Rica), C. unispina (Costa Rica, Panama), and C. vexillifera (Guatemala).